Outcome after Lateral Pancreaticojejunostomy for Chronic Calcific Pancreatitis: A Short Term Prospective Study (Journal of Shaheed Suhrawardy Medical College, 2019)
Chronic pancreatitis is a fairly common condition with pain being the major symptom and longitudinal pancreaticojejunostomy (LPJ) is performed for symptomatic relief. The aim of the study is to assess the outcome of LPJ for chronic calcific pancreatitis and to evaluate the factors influencing relief of symptoms. A prospective observational study enrolling 28 patients was conducted in the department of surgery of Shaheed Suhrawardy Medical College Hospital from January 2018 to December 2018. This study involved identification of various risk factors related to chronic pancreatitis, pancreaticojejunostomy, early post-operative outcome and postoperative assessment of pain relief at 1 and 6 months from surgery. Pain was assessed using Visual analogue scale (VAS). In chronic pancreatitis, there is a significant relief of pain in post-LPJ; the degree of relief was less in the alcoholics than non-alcoholics (p=0.09) and in smokers. There was also reduction in analgesic requirement and frequency of acute attacks of pain. In chronic pancreatitis, there is a significant relief of pain in post-LPJ, although the degree of relief is less in the alcoholics and smokers.J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 13-16